Desert War the battle of Sidi Rezegh - Cox, Peter (ANZAC battles series, 2015)
Sir Geoffrey Cox described Sidi Rezegh, fought during Operation Crusader in Libya over November and December 1941, as 'the forgotten battle of the Desert War'. The objective of Crusader was to retake Cyrenaica, the eastern region of Libya, and ultimately drive the Italians and Germans out of North Africa. The campaign also involved British and South African troops, and did achieve the badly needed relief of Tobruk. Despite the importance of this campaign in achieving British victory in North Africa, it has largely been neglected by historians, failing to receive as much attention as Crete, El Alamein or Cassino. Yet more New Zealand soldiers were killed or taken prisoner during Crusader than in any other campaign fought by 'the Div' during the war. Peter Cox, whose father fought at Sidi Rezegh, draws on his experience of twice visiting the battlefield to tell the story of this complex, costly campaign. He sets the scene for the fighting in Libya, describes the unforgiving and inhospitable desert landscape, follows the stages of the action itself and recounts the often moving and heroic stories of the those who fought there. Many never returned home. This is both an accessible account of a significant New Zealand contribution to World War II and a tribute to the thousands of men who took part in this punishing battle